REPRESENTASI GAYA HIDUP MAHASISWA DALAM NOVEL GOOD MEMORIES KARYA LIA INDRA ANDRIANA - Vacliuca, Queentha; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
All aspects of student life and lifestyle, reflected on the Indonesia literary works.Literature was born in the middle of the mayarakat as a result of the author's imaginationand reflection against the social symptoms. Therefore a literary work in daulat part ofpeople's lives. A good work of literature not only record the fact that exist in society, but alsorecord and depicts reality in its entirety. The purpose of this research is to know thecharacter of the people who participate in the plot represent the lifestyle of students in thenovel Good Memories work of Lia Indra Andriana.This research uses qualitative research methods through the analysis of narrative.Data collection techniques taken from the novel the Good Memories published in 2013 whichconsists of 22 chapters and 336 pages. Data analysis use analysis of narrative by twoexperts, namely Vladimir Propp and Tzvetan Todorov. The core narrative analysis iscombining the two dimensions of the narrative that is a character and plot into one unifiedanalysis.The results showed that the presence of representation of students ' lifestyle in thenovel Good Memories work of Lia Indra Andriana. The existing figures in the novel GoodMemories is Maya, and Luc as the main character and other characters namely Rani,Professor Ahn, Alva, Yujin and Maya’s father. The plot is told in the novel Good Memoriesusing advanced flow with flow structure is an introduction, middle, and settlement. Researchdescribes and outlines any opinion through a form of narrative that describes and representthe lifestyle of students as a form of narrative analysis studies in the novel Good Memorieswork of Lia Indra Andriana.Keywords : Narrative Analysis, Representation, Lifestyle, Student, Novel